2016
DOI: 10.1371/journal.pone.0156667
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Nucleic Acid Polymers in Monotherapy and Combined with Immunotherapy in Treatment-Naive Bangladeshi Patients with HBeAg+ Chronic Hepatitis B Infection

Abstract: Previous in vivo studies have suggested that nucleic acid polymers (NAPs) may reduce circulating levels of HBsAg in the blood by blocking its release from infected hepatocytes and that this effect may have clinical benefit. NAP treatment, was evaluated in two clinical studies in patients with HBeAg positive chronic HBV infection. The REP 101 study examined REP 2055 monotherapy in 8 patients and the REP 102 study examined REP 2139-Ca, in monotherapy in 12 patients, 9 of which transitioned to short term combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
213
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 160 publications
(237 citation statements)
references
References 36 publications
19
213
3
2
Order By: Relevance
“…Based on the chemical modifications present in REP 2006 and REP 2055 their intermediate stability relative to REP 2139 and REP 216525 will result in liver accumulation for these NAPs within the limits observed for REP 2139 and REP 2165 but will have the same rapid clearance characteristics from the plasma. In all clinical assessments of REP 2055, REP 2139 and REP 2165 performed to date, substantial HBsAg reductions and or clearance is achieved well within 3 months52829 well before any immunostimulatory or pro-inflammatory activity would be predicted to occur based on pharmacokinetics in non-human primates and the weak pro-inflammatory and immunostimulatory properties of NAPs observed in this study.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Based on the chemical modifications present in REP 2006 and REP 2055 their intermediate stability relative to REP 2139 and REP 216525 will result in liver accumulation for these NAPs within the limits observed for REP 2139 and REP 2165 but will have the same rapid clearance characteristics from the plasma. In all clinical assessments of REP 2055, REP 2139 and REP 2165 performed to date, substantial HBsAg reductions and or clearance is achieved well within 3 months52829 well before any immunostimulatory or pro-inflammatory activity would be predicted to occur based on pharmacokinetics in non-human primates and the weak pro-inflammatory and immunostimulatory properties of NAPs observed in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Here slight but significant induction of IFNA4 and IFNL2 gene expression was observed that did not result in interferon secretion. The antiviral effects of NAPs, namely the reduction of serum HBV surface antigen in HBV-infected patients are very similar for REP 2055, REP 2139 and REP 216552829 despite the absence (REP 2055) or presence (REP 2139 and REP 2165) of 2′OMe and 5MeC modifications. It should be noted that although an increase in inflammatory cytokine gene expression in PBMCs is significant for all NAPs, cytokine secretion was only weakly stimulated for REP 2055 and REP 2139 (and not with REP 2165) and was only observed with NAP concentrations about 5-fold greater than their C max in cymologus monkeys, which is short lived.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The success rate of these treatments is low. Several candidates are being evaluated in clinical trials mainly in combination with PegIFNa and/or NA including HBV/HDV entry inhibitors (Myrcludex-B), 244,245 drugs inhibiting the release of HBsAg (nucleic acid polymers), 246 and inhibitors of the prenylation of the large HDV antigen. 243,247 Whenever possible, enrollment in these new clinical trials should be considered, either as a rescue of PegIFNa failure or to improve treatment success rate in naïve patients.…”
Section: Future Treatment Options For Hdvmentioning
confidence: 99%
“…Their activity is driven by interactions with large amphipathic protein domains important for viral replication and relies only on the length of the oligonucleotide (optimally 40-mer) and the presence of phosphorothioation 1 . The NAP REP 2139 is currently in clinical development for the treatment of chronic hepatitis B (HBV) infection and HBV/hepatitis delta (HDV) co-infection and has shown a unique ability to clear the HBV surface antigen (HBsAg) from the blood in clinical trials 2, 3, 4. This activity is driven by the ability of NAPs to block the release of HBsAg from infected hepatocytes, likely by interfering with the assembly of HBV subviral particles 5 by an as yet undefined mechanism.…”
Section: Introductionmentioning
confidence: 99%